Flexible Organic Crystals for Dynamic Optical Transmission - Lan, Linfeng (2023)
In recent years, studies of organic optical waveguide materials have emerged as a cutting-edge research area driven by their inherent advantages, such as low optical losses, structural versatility, and attractive optical properties. Notably, organic crystals exhibiting a high refractive index and optical transparency have gained attention as prospective materials for next-generation optoelectronic devices. However, unlike viscoelastic polymers with flexible chains, organic single crystals composed of densely arranged anisotropic organic small molecules have not been considered viable as functional materials due to their mechanical rigidity and fragility. Recently, the solid-state research community has witnessed a breakthrough in developing flexible organic crystalline materials, bringing a unique class of soft yet ordered engineering materials with plasticity or elasticity poised to revolutionize the concept of organic crystalline electronics. Recent works have demonstrated the feasibility of flexible organic crystals in optical transmission and have developed a variety of elastic organic crystals with different structures and functions, opening up opportunities for the design of flexible single-crystalline electronic devices. The first elastic organic crystalline optical waveguide has been prepared by building on the elasticity and luminescent properties of such organic crystals. Subsequently, various flexible organic crystals have been discovered and reported, enabling the realization of self-doped crystal waveguides, three-dimensional optical waveguides, phosphorescent waveguides, polarization rotators, and other optical elements. Through molecular design strategies, such as the construction of π-conjugated systems and introduction of heteroatoms, as well as by employing the principles of crystal engineering, researchers have developed flexible crystalline waveguiding materials with extraordinary mechanical properties, including elastic or thermoplastic bending and stimulus-specific deformation. The applications of these optically functional flexible organic crystals have been extended to low/high-temperature environments. Furthermore, combining flexible organic crystals with inorganic/polymeric materials by self-assembly techniques has led to the development of new hybrid functional materials such as solvent-resistant-coated crystals, humidity- and temperature-responsive actuators, and magnetically controllable hybrid materials. These advancements have paved the way for novel applications of organic crystals in flexible devices, such as sensors, soft robots, and optoelectronic devices.